A whole ecosystem approach to pear psyllid (Cacopsylla pyri) management in a changing climate - Laura A. Reeves; Michael P. D. Garratt; Michelle T. Fountain; Deepa Senapathi (Journal of Pest Science, 2024)
Whole ecosystem-based approaches are becoming increasingly common in pest management within agricultural systems. These strategies consider all trophic levels and abiotic processes within an ecosystem, including interactions between different factors. This review outlines a whole ecosystem approach to the integrated pest management of pear psyllid ( Cacopsylla pyri Linnaeus) within pear ( Pyrus communis L.) orchards, focusing on potential disruptions as a result of climate change. Pear psyllid is estimated to cost the UK pear industry £5 million per annum and has a significant economic impact on pear production globally. Pesticide resistance is well documented in psyllids, leading to many growers to rely on biological control using natural enemies during the summer months. In addition, multiple insecticides commonly used in pear psyllid control have been withdrawn from the UK and Europe, emphasising the need for alternative control methods. There is growing concern that climate change could alter trophic interactions and phenological events within agroecosystems. For example, warmer temperatures could lead to earlier pear flowering and pest emergence, as well as faster insect development rates and altered activity levels. If climate change impacts pear psyllid differently to natural enemies, then trophic mismatches could occur, impacting pest populations. This review aims to evaluate current strategies used in C. pyri management, discuss trophic interactions within this agroecosystem and highlight potential changes in the top-down and bottom-up control of C. pyri as a result of climate change. This review provides a recommended approach to pear psyllid management, identifies evidence gaps and outlines areas of future research.